Anal Atresia and Structural Malformations of the Perineum and Anus in a Mare - Ferreira, Manoel Luiz; Filho, Fernando Alzamora; Silva, Marcus Vinícius Alves da; Silva, Paulo Cesar; Eulálio, José Marcus Raso; Manso, José Eduardo Ferreira; Silva, Carolina Viviani Freitas da; Schanaider, Alberto (Acta Scientiae Veterinariae, 2020)
Background: Anal atresia is a congenital defect and is related to the flaw of an opening in the membrane that separates the endoderm of the posterior intestine from the ectodermic anal membrane. This anomaly can cause debilitating disease, death, or abnormal development of the animal. Clinical presentation of urethrorectal fistula in domestic animals differs between males and females, as in the former there is passage of the urine through the anus, whereas in females there is elimination of the feces through the vulva. The absence of description of this disease in horses stimulated describing a case of surgical resolution of anal atresia, rectal bulb agenesis, and pneumovagina of an adult mare. Case: Mare with a history of defecating through the vagina. In the anamnesis, it was determined that the owner noticed the problem after observing the animal during a walk. Clinical examination verified absence of the anus with stool evacuation through the vagina, pneumovagina, and signs of cystitis, as the animal frequently urinated small volumes. Complementary laboratory tests of blood and urine were carried out for the diagnosis of cystitis, serum biochemistry, hemogram, and urinalysis being evaluated. The operation was scheduled for eight days after clinical tests and sodium ceftiofur was prescribed, at a dose of 4.4 mg/kg, administered intramuscularly for seven days. On the date chosen for surgical intervention, the animal was fasted for the previous 12 h; procedures began with the containment of the animal in a stock, followed by pre-anesthesia with detomidine, at a dose of 20 µg/kg, administered intravenously in solution at 1%. Anesthesia was a low peridural with 2% lidocaine at a total dose of 15 mL, to be able to work in the quadruped position. After containment of the tail and taking antiseptic and aseptic care, sutures were made in the skin and vaginal mucous, as it exhibited a solution of continuity. In the mucous, suture consisted of separate simple stitches made with perforation needle and 2-0 polyglactin 910 suture, while in the skin Wolff stitches were applied using a blade needle and 2-0 nylon suture. Then, a circular incision was made in the skin in the anus region to remove local skin; this revealed the rectum which, being it far from the required location, was pulled to the new opening. The rectum was fixed to the skin by suture: four simple stiches, with a perforation needle and zero nylon suture, to serve as repairs, followed by simple stitches between the repairs, with the same type of suture. Regarding the pneumovagina, reconstruction of the perineum and application of modified Calisck surgical technique were performed to correct the vulva defect. In the post-operative phase, 4.4 mg/kg of sodium ceftiofur was administered intramuscularly for seven days, and Flunixin Meglumine, at a dose of 1.1 mg/ml for every 50 kg of body weight, was administered intravenously for four days. Furthermore, rectal enemas (3 L of warm aqueous solution associated with glycerin) were administered every eight hours for 14 consecutive days, and the wound was cleaned with 2% chlorhexidine degerming solution. The skin sutures were removed after 15 days and the animal was discharged. Discussion: Alteration of the digestive tract in horses presents nuances in genetic dependence, embryology, and congenital defects, among others. Regarding the possibility of surgical correction, it is necessary to observe the characteristics of the lesion, the handling to which the animal is subjected, care of the surgical wound, and physical conditions where surgical procedures are carried out. The results obtained with this intervention and pre-, trans-, and post-operative care were effective in reestablishing the patient.